Decline of rental housing in India: the case of Mumbai. (April 2016) - Tandel, Vaidehi; Patel, Shirish; Gandhi, Sahil; Pethe, Abhay; Agarwal, Kabir
The amount of rental housing in India has declined significantly over the years for various reasons, including the nature of the rent control laws. This paper assesses the impact of rent control for Mumbai, where it has created a shortfall in formal, affordable rental housing and contributed to distortions in the land market. The paper describes how "first-generation" rent control in Mumbai has led to deterioration of the existing rental housing stock, virtually halted the construction of new housing for rental in the city, and given rise to informal practices such as pagdi or key money. It also analyses the spatial concentration and composition of rent-controlled tenements in the city. It proposes reforms that would allow a gradual move towards rationalized rent controls, arguing that such second-generation controls will help incentivize investments in the rental sector and reduce the demand in the housing market at large, with implications for prices and affordable housing in particular.